2014
DOI: 10.1007/s12672-014-0195-9
|View full text |Cite
|
Sign up to set email alerts
|

The G Protein-Coupled Estrogen Receptor-1, GPER-1, Promotes Fibrillogenesis via a Shc-Dependent Pathway Resulting in Anchorage-Independent Growth

Abstract: The G protein-coupled estrogen receptor-1, GPER-1, coordinates fibronectin (FN) matrix assembly and release of heparan-bound epidermal growth factor (HB-EGF). This mechanism of action results in the recruitment of FN-engaged integrin α5β1 to fibrillar adhesions and the formation of integrin α5β1-Shc adaptor protein complexes. Here, we show that GPER-1 stimulation of murine 4 T1 or human SKBR3 breast cancer cells with 17β-estradiol (E2β) promotes the formation of focal adhesions and actin stress fibers and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 78 publications
2
14
0
Order By: Relevance
“…Hence, the results obtained in the present study further suggest that GPER1 may mediate the effects of E 2 on neurite outgrowth in hfNBMs, as reported previously . Moreover, our findings appear to be in agreement with the demonstration that GPER1 stimulation with E 2 in different cellular systems (eg, breast cancer cells) promotes the formation of focal adhesions leading to the reorganisation of actin stress fibres and enhanced cellular adhesivity …”
Section: Discussionsupporting
confidence: 93%
“…Hence, the results obtained in the present study further suggest that GPER1 may mediate the effects of E 2 on neurite outgrowth in hfNBMs, as reported previously . Moreover, our findings appear to be in agreement with the demonstration that GPER1 stimulation with E 2 in different cellular systems (eg, breast cancer cells) promotes the formation of focal adhesions leading to the reorganisation of actin stress fibres and enhanced cellular adhesivity …”
Section: Discussionsupporting
confidence: 93%
“…E2 ligand binds to GPR30, making the G protein heterotrimeric disintegration into Gα and Gβγ. Gβγ can activate Src phosphorylation, thereby promote the cell membrane MMP, leading to HB‐EGF releasing and playing a role as a ligand to activate EGFR, therefore activation of its downstream signaling pathway, such as MAPK, ERK, PI3K, increased c‐fos and other transcriptional gene expression, thereby promoting cell proliferation and differentiation …”
Section: Discussionmentioning
confidence: 99%
“…thrombin and epinephrine) or chemokines interact with their respective GPCRs to regulate the affinity of platelet or leukocyte integrins to promote thrombus formation and leukocyte extravasation, respectively [Ginsberg et al, 2005;Luo et al, 2007]. Similarly, estrogen acts via GPER to promote the recruitment of integrin α5β1 to fibrillar adhesions, specialized adhesions sites that promote fibronectin fibril formation "fibrillogenesis" and ultimately, fibronectin matrix assembly and anchorage-independent growth [Quinn et al, 2009;Magruder et al, 2014]. Moreover, we have shown that integrin α5β1 is a necessary transmembrane signaling component for GPER dependent exoplasmic release of proHB-EGF suggests a common mechanism by which GPER may coordinate integrin-matrix adhesion, the assembly of a provisional fibronectin matrix and the local release of EGF-related polypeptides [Quinn et al, 2009;Magruder et al, 2014].…”
Section: Gper: Estrogen Mediated Actions and Cell Biological Functionsmentioning
confidence: 99%
“…Similarly, estrogen acts via GPER to promote the recruitment of integrin α5β1 to fibrillar adhesions, specialized adhesions sites that promote fibronectin fibril formation "fibrillogenesis" and ultimately, fibronectin matrix assembly and anchorage-independent growth [Quinn et al, 2009;Magruder et al, 2014]. Moreover, we have shown that integrin α5β1 is a necessary transmembrane signaling component for GPER dependent exoplasmic release of proHB-EGF suggests a common mechanism by which GPER may coordinate integrin-matrix adhesion, the assembly of a provisional fibronectin matrix and the local release of EGF-related polypeptides [Quinn et al, 2009;Magruder et al, 2014]. As a consequence of its capacity to transactivate both integrin and EGFRs, GPER is strongly positioned to promote cellular survival responses, cell biological effects that fit well with the physiological and pathological processes that have been linked to GPER.…”
Section: Gper: Estrogen Mediated Actions and Cell Biological Functionsmentioning
confidence: 99%
See 1 more Smart Citation